Community Empowerment Strategies Through Organic Farming in Papringan Village, Kaliwungu Sub-district, Kudus Regency - Maulindha Sari, Khoidatul (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
Organic farming is a cultivation system that prioritizes ecological balance and environmental sustainability by not using synthetic chemicals such as pesticides and artificial fertilizers. In contrast to conventional agriculture which often relies on external inputs to increase production yields, organic agriculture emphasizes the use of natural resources in a natural and sustainable manner. The purpose of this research is to find out the description of organic farming and community empowerment through organic farming activities in terms of economic value or other values. This type of research is Qualitative using Miles Huberman analysis. The results showed that organic farming in Papringan village has been running well with the proof that the types of plants cultivated such as bananas, chilies and longan produce a stable harvest. These crops can have high economic value, but also have good health value. So that this organic farming activity as a form of community empowerment can be a community option to maintain living standards.